Localisation of unresolved targets with frequency divers array radar - Shengbin Luo Wang; Zhenhai Xu; Xinghua Liu; Wei Dong; Guoyu Wang (The Journal of Engineering, 2019)
The results of angular and range estimation by conventional signal processing will be far away from true values in the case of unresolved targets due to the merged measurement. In this article, the authors propose a method to localise unresolved targets for frequency diverse array (FDA) radar. Adopting the configurations of subarray-based FDA and full-band FDA as transmitter and receiver, the transmit and receive beampatterns of system are both decoupled in range and angle demands. Furthermore, the receive beamwidth is only a quarter of transmit in range. With the wide transmit beam and narrow receive beam, the authors divide the resolution cell containing unresolved targets into four parts to process separately. A method of intra-pulse beam scanning is proposed to suppress the interference from the targets out of receive beam. Several simulation results demonstrate the effectiveness of the proposed method in the localisation of unresolved targets.